Music Therapy to Reduce Angry Emotions in People with Mental Disorders: Terapi Musik untuk Mengurangi Emosi Marah pada Orang dengan Gangguan Mental - Wulandari, Dwi Retno; Laili, Nurfi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Mental health is a crucial component of overall well-being, yet mental disorders remain highly prevalent and often manifest through negative emotional expressions such as anger. Specific Background: People with mental disorders (ODGJ) in social institutions frequently express anger in disruptive ways, affecting their daily functioning and care environment. Knowledge Gap: Despite the use of various therapies, limited research has focused on structured music therapy as a tool to reduce anger among ODGJ in Indonesian social facilities. Aim: This study investigates whether music therapy can reduce angry emotional behavior in ODGJ at Liponsos Sidoarjo. Results: Using a quantitative pre-experimental One Group Pretest-Posttest design with two subjects, data were collected through observation using a behavior checklist and analyzed with descriptive statistics and the Mann-Whitney U Test. Results indicated a significant reduction in anger behavior (W = 57.5, p = 0.028). Novelty: Unlike prior studies that specify certain music genres, this research employed a mix of songs based on patient preference, demonstrating flexibility in therapy application. Implications: Findings suggest that music therapy can be an effective intervention for reducing anger in ODGJ, with potential integration into routine care programs at social institutions. Highlights: Music therapy reduced anger in ODGJ Flexible song choices enhanced engagement Applicable for social institution settings Keywords: Music Therapy, Angry Emotions, Mental Disorder, ODGJ, Intervention